CONCORDANCE BETWEEN TWO QUESTIONARIES FOR THE DIAGNOSIS OF DIGITAL EYE STRAIN IN STUDENTS OF A UNIVERSITY IN PERU: CONCORDANCIA ENTRE DOS ENCUESTAS PARA EL DIAGNÓSTICO DE FATIGA VISUAL DIGITAL EN ESTUDIANTES DE UNA UNIVERSIDAD EN PERÚ - Landa Guerra, Guillermo (2024)
Objective: Obtain the frequency of digital eye strain (DES) between two questionnaires among students of a private university in Lima, Peru; in order to estimate the degree of concordance between both methods. Methods: A cross-sectional study was carried out in a sample of 345 participants over 18 years of age, students at a university in Lima, Peru, and who completed the data collection instrument. The two methods used to measure DES were the Hayes questionnaire, which defines a positive case for DES with a score equal to or greater than 20; and the CVS-Q questionnaire of Seguí, which defines a score greater than 6 as positive for DES. Cohen's kappa coefficient was estimated with its 95% confidence interval to measure global concordance degree and by groups. Results: The Hayes questionnaire identified 167 (48.4%) participants with a presumptive diagnosis of DES, the Seguí questionnaire identified 247 (71.6%) students. In the concordance analysis, Cohen's Kappa coefficient was 0.45 (95% CI; 0.37 – 0.53) (p < 0.01) in the global analysis, considered as moderate. Conclusion: The degree of concordance between both methods was moderate, the Seguí instrument identified a higher proportion of university students with FVD.